2010
DOI: 10.1111/j.1445-2197.2010.05334.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of the Delphian and level VI nodes in papillary thyroid cancer

Abstract: This is the first study to examine the diagnostic accuracy of all level VI lymph nodes in PTC. While, metastatic involvement of all central nodal groups is indicative of further disease, the DLN is the most accurate predictor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 36 publications
(63 reference statements)
4
52
0
Order By: Relevance
“…In addition, some studies have revealed that prelaryngeal LN involvement was highly predictive of further nodal metastasis to the central and lateral neck compartments [23][24][25]. Prelaryngeal LN positivity was also associated with the number of metastatic nodes and nodal size [26].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…In addition, some studies have revealed that prelaryngeal LN involvement was highly predictive of further nodal metastasis to the central and lateral neck compartments [23][24][25]. Prelaryngeal LN positivity was also associated with the number of metastatic nodes and nodal size [26].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…It could be used as a predictor for recurrence or metastasis of thyroid cancer whose predict accuracy was apparently higher than the pretracheal and paratracheal node. 16 His following research in 2009, in which more PTC patients were enrolled, revealed that central node metastasis was an important predictor for recurrence or metastasis of PTC, especially DLN, which was more accurate. In 2012, Woo Woong Kim gathered more cases of PTC with DLN metastasis and found the rate of DLN metastasis was 17.2%.…”
Section: Discussionmentioning
confidence: 98%
“…However, the process does increase the extent of wounding in PTC patients without the 2 subgroups of LN metastasis. Moreover, it has been reported that the involvement of the prelaryngeal central LN is the most accurate predictor of lateral node disease [30]. …”
Section: Discussionmentioning
confidence: 99%